The impact of process planning on cost and production losses in additive manufacturing - Basak, Shreeja (2023)
Additive Manufacturing (AM) is a class of manufacturing techniques that relies on joining material, layer-upon-layer, to create the final object. With significantly lower barriers to manufacturing-on-demand and fulfilling product variety, AM is predicted to cause a disruptive revolution in manufacturing and product-service industries. However, mainstream adoption of AM, particularly at scale, is hindered by a lack of suitable operations management understanding, exacerbating issues related to productivity and high cost. Therefore, this thesis attempts to provide a path towards efficient AM operations at scale. This is done by addressing key process efficiency concerns via operations management interventions and thus developing best practice recommendations for AM users.